Internal Consistency of Yesavage Geriatric Depression Scale (GDS 15-Item Version) in Ecuadorian Older Adults - María Erazo MD; Martha Fors PhD; Sofía Mullo MD; Paloma González; Carmen Viada MSc (SAGE Publishing, 2020)
The present study aimed to assess the validity of a Spanish version of the Geriatric Depression-15 Scale (GDS-15) in Ecuadorian adults. Cross-sectional study to validate GDS-15 in its short version (GDS-15). Internal consistency and factor structure were assessed through Kuder Richardson 20 and Confirmatory Factor Analysis. A total of 211 subjects 65 years of age and older participated in the validation process. Internal consistency was adequate, the Kuder Richardson 20 coefficient for the total scale was 0.73. Three factor structure was found for the scale. This study highlights the importance of having a validated scale for screening depression in the elderly. This study provides an evidence for the use of GDS-15 in Ecuadorian elderly population to screen for depression.